Updating the Role of α-Cell Preproglucagon Products on GLP-1 Receptor–Mediated Insulin Secretion - Sandoval, Darleen (Diabetes, 2020)
While the field of islet biology has historically focused its attention on understanding β-cell function and the mechanisms by which these cells become dysfunctional with diabetes, there has been a scientific shift toward greater understanding of other endocrine cells of the islet and their paracrine role in regulating the β-cell. In recent years, many questions and new data have come forward regarding the paracrine role of the α-cell and specifically preproglucagon peptides in regulating insulin secretion. The role of intestinally secreted glucagon-like peptide 1 (GLP-1) in regulation of insulin secretion has been questioned, and a physiological role of pancreatic GLP-1 in regulation of insulin secretion has been proposed. In addition, in the last 2 years, a series of studies demonstrated a physiological role for glucagon, acting via the GLP-1 receptor, in paracrine regulation of insulin secretion. Altogether, this work challenges the textbook physiology of both GLP-1 and glucagon and presents a critical paradigm shift for the field. This article addresses these new findings surrounding α-cell preproglucagon products, with a particular focus on GLP-1, in the context of their roles in insulin secretion and consequently glucose metabolism.